Confusion about the 2004 increase in the number of training places - Flemming, Simone [Verfasser]; Uhly, Alexandra [Verfasser]; Ulrich, Joachim Gerd [Verfasser] (My University, 2005)
"At the end of 2004 the Federal Ministry of Education and Research (BMBF) disclosed the results of the BIBB survey on newly concluded training contracts for the placement year 2004. According to this survey the number of new training contracts increased countrywide by more than 15,300 over 2003, the first increase since 1999. There were about 14,100 more contracts in the west, and in the east the increase amounted to about 1,200." (BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; Ausbildungsstellenmarkt; Ausbildungsvertrag; Berufsbildungsstatistik; 2004